Tuan Guru Leadership in Cultural Transformation of Rebo Bontong - Arifin, Muhamad (Universitas Djuanda, 2025)
This study analyzes the dynamics of Islamic education in Lombok through the leadership of Tuan guru in the cultural transformation of Rebo Bontong at Islamic Boarding School (Pesantren) Darul Falah Mataram, focusing on how Tuan guru directs the shift of cultural practices that are less aligned with Islamic values into religious rituals that reinforce the teachings of Tasawwuf and Ahlussunnah wal Jama'ah. The study employs Bernard M. Bass's transformational leadership theory, Kurt Lewin's change theory, and Clayton Alderfer's motivation theory as its theoretical framework. As a spiritual leader and a mursyid of the Qadiriyah wa Naqsyabandiyah order, Tuan guru plays a crucial role not only in religious education but also in shaping social and economic changes within the community. Using a qualitative method with a descriptive approach, this study involves participatory observation, in-depth interviews, and document analysis. The findings revealed that Tuan guru’s leadership significantly influenced three key aspects: first, charismatic leadership that guided santri and the community towards Islamic practices more in line with religious teachings; second, intellectual stimulation through the enhancement of santri literacy and the dissemination of dakwah bil-kitabah via the Najmul Huda bulletin; and third, motivation and individual care through the economic empowerment of the pesantren and the surrounding community. The cultural transformation of Rebo Bontong not only eliminated elements that contradicted Islamic teachings but also strengthened the religious identity of the Lombok community. This study confirmed that the cultural and spiritual approach applied by Tuan guru served as an effective model for reforming local traditions without triggering social resistance. These findings contribute to the study of Islamic leadership and the revitalization of religious traditions within the Muslim communities of the Nusantara.